My Therapist / Ahmad Syahmi Isa ... [et al.] - Isa, Ahmad Syahmi; Hassan, Muhammad Akim; Zuraidi, Muhammad Amirul Hakim; Jahya, Mohamad Azim (2021)
My Therapist provides massage therapy and cupping in their business for the people who are interested in getting this service. This treatment responds to an increasing body of research literature that documents the effectiveness of massage therapy in both the mental and health and substance abuse treatment fields. Cupping therapy is a physical treatment which refers to a technique that uses small glass cups as suction devices that are placed on our skin. Cupping believed to have potential benefit in treating myriad types of disease and conditions. For this task, we have chosen My Therapist for the interview as their staff is friendly and supportive and makes our interview session run smoothly. Every information given which is on the company information is very beneficial for us to take it for doing this task. Thus, all the information is being taken to find the problem that the company has occurred during their production time. Last but not least, My Therapist promotes their service by using social media like Facebook page and the posters as their main platform.